Breakthrough Energy Technologies Toward a Solution for Climatic Change - Valone, Thomas F. (European Journal of Applied Sciences, 2022)
In this age of climate change, the corporate, academic, and government research into new, green sources of power and energy still has not been well-funded nor forthcoming in this century. This presentation will review some of the best emerging energy technologies that promise green and carbon-free sustainable generation as well as food and water energy innovations, including a bioenergetics discovery. Progress is being made presently by academic and industry that will create a future having greater ease in newly developed renewable energy generation with much better, localized energy sources that do not use fossil fuel for power and heat. Beyond the realm of fuel cells and wind power is the non- conventional world of emerging energy technologies. Some of the best examples are new and exciting generators that release trapped potential energy from nature in ways never dreamed of before. Others innovatively apply clean fuels in conventional systems that are the focus of attention for NASA, DARPA, and the USDOE. Some of the more exotic examples include a recent breakthrough with graphene energy harvesting, which has thermal and nonthermal (quantum vacuum) sources to it. This illustrated slideshow presentation summarizes the research that has been accomplished so far in the development of highly efficient, energy harvesting inventions, as well as other future energy breakthroughs. The most exciting reason for the interest in this area of research is the promise that it holds for boosting electric vehicle production by providing an onboard electric battery charger. These energy generation developments, derived from relatively new paradigm science discoveries, also have many other applications, including a design for rural stand-alone electrical generators. Most of them have one thing in common: they are relatively unknown to the general public.